Transcriptome Analyses Reveal IL6/Stat3 Signaling Involvement in Radial Glia Proliferation After Stab Wound Injury in the Adult Zebrafish Optic Tectum - Shimizu, Yuki; Kiyooka, Mariko; Ohshima, Toshio (Frontiers in Cell and Developmental Biology, 2021)
Adult zebrafish have many neurogenic niches and a high capacity for central nervous system regeneration compared to mammals, including humans and rodents. The majority of radial glia (RG) in the zebrafish optic tectum are quiescent under physiological conditions; however, stab wound injury induces their proliferation and differentiation into newborn neurons. Although previous studies have functionally analyzed the molecular mechanisms of RG proliferation and differentiation and have performed single-cell transcriptomic analyses around the peak of RG proliferation, the cellular response and changes in global gene expression during the early stages of tectum regeneration remain poorly understood. In this study, we performed histological analyses which revealed an increase in isolectin B4+ macrophages prior to the induction of RG proliferation. Moreover, transcriptome and pathway analyses based on differentially expressed genes identified various enriched pathways, including apoptosis, the innate immune system, cell proliferation, cytokine signaling, p53 signaling, and IL6/Jak-Stat signaling. In particular, we found that Stat3 inhibition suppressed RG proliferation after stab wound injury and that IL6 administration into cerebroventricular fluid activates RG proliferation without causing injury. Together, the findings of these transcriptomic and functional analyses reveal that IL6/Stat3 signaling is an initial trigger of RG activation during optic tectum regeneration.